Development of eco-friendly fire-retarded warm-mix epoxy asphalt binders using reactive polymeric flame retardants for road tunnel pavements. (17th May 2021) - Chen, Ru; Zhao, Ruikang; Liu, Ya; Xi, Zhonghua; Cai, Jun; Zhang, Junsheng; Wang, Qingjun; Xie, Hongfeng
Graphical abstract: Highlights: Eco-friendly fire-retarded warm-mix epoxy asphalt binders (WEABs) have been developed. RPFR of significantly improved the fire retardancy of the pure WEAB. RPFR hinders WEAB's cure reaction and extends the allowable construction time of WEAB mixtures. RPFR improves the glass transition temperature and thermal stability of the pure WEAB. Double phase separation forms in RPFR modified WEABs. Abstract: Epoxy asphalt binder is flammable and plenty of fumes are produced during its high-temperature pavements in tunnels. To improve fire retardancy and reduce asphalt fumes, eco-friendly flame-retarded warm-mix epoxy asphalt binders (WEABs) for road tunnel pavements were developed by incorporation of reactive polymeric flame retardant (RPFR), which was composed of a reactive polymeric brominated epoxy oligomer (BEO) and antimony oxide. The influence of RPRF on flame retardancy, rotational viscosity, microstructures, thermal properties and mechanical performance of the pure WEAB was investigated using various techniques: oxygen index instrument, Brookfield viscometer, confocal microscope, differential scanning calorimeter, thermogravimetric analyzer and universal testing machine. The presence of RPFR significantly improved the limited oxygen index (LOI) of the pure WEAB. The LOI of RPFR modified WEABs increased in the flame retardant loading. The reaction of epoxide groups of RPFR with the curing agents of epoxy asphalt reduced the viscosity of the pure WEAB and extended the allowable construction time of the WEAB mixture. The inclusion of RPFR increased the glass transition temperature (Tg ) of the pure WEAB. For modified WEABs, the Tg increased in the RPFR loading. RPFR reacted into the epoxy asphalt backbone through the reaction between epoxy groups and curing agents. The incorporation of RPFR improved the thermal stability of the pure WEAB. The addition of 8 wt% RPFR increased the tensile strength of the pure WEAB, while the inclusion of RPFR slightly decreased the break elongation of the pure WEAB. Double phase separation occurred in RPFR modified WEAB: the main phase separation included the continuous epoxy phase and the discontinuous asphalt domains, in which the secondary phase separation formed with asphalt as the continuous phase and spherical BEO domains as the discontinuous phase. The particle size of BEO domains decreased with the increase of the RPFR loading.